Detection and quantification of citrullinated chemokines. - Eva A V Moelants (Public Library of Science (PLoS), 2011)
Background Posttranslational deimination or citrullination by peptidylarginine deiminases (PAD) regulates the biological function of proteins and may be involved in the development of autoimmune diseases such as rheumatoid arthritis and multiple sclerosis. This posttranslational modification of arginine was recently discovered on inflammatory chemokines including CXCL8 and CXCL10, and significantly reduced their biological activity. To evaluate the importance of these modified chemokines in patients, methods for the detection and quantification of citrullinated chemokines are needed. Since citrullination only results in an increase of the protein mass with one mass unit and the loss of one positive charge, selective biochemical detection is difficult. Therefore, we developed an antibody-based method to specifically detect and quantify citrullination on a protein of interest. Methodology/principal findings First, the citrullinated proteins were chemically modified with antipyrine and 2,3-butanedione at low pH. Such selectively modified citrullines were subsequently detected and quantified by specific antibodies raised against a modified citrulline-containing peptide. The specificity of this two-step procedure was validated for citrullinated CXCL8 ([Cit(5)]CXCL8). Specific detection of [Cit(5)]CXCL8 concentrations between 1 and 50 ng/ml was possible, also in complex samples containing an excess of contaminating proteins. This novel detection method was used to evaluate the effect of lipopolysaccharide (LPS) on the citrullination of inflammatory chemokines induced in peripheral blood mononuclear cells (PBMCs) and granulocytes. LPS had no significant effect on the induction of CXCL8 citrullination in human PBMCs and granulocytes. However, granulocytes, known to contain PAD, were essential for the production of significant amounts of [Cit(5)]CXCL8. Conclusion/significance The newly developed antibody-based method to specifically detect and quantify chemically modified citrullinated proteins is proven to be effective. This study furthermore demonstrates that granulocytes were essential to obtain significant levels of [Cit(5)]CXCL8. For human PBMCs and granulocytes stimulation with LPS did not affect the citrullination of CXCL8.